CLINICAL PHARMACOLOGY OF GLUCOCORTICOID DRUG USE IN CHILDREN OLDER THAN 2 YEARS - Ababakirov Khamdambek Yusupovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article presents an in-depth review of the clinical pharmacology of glucocorticoid therapy in pediatric patients older than two years. Glucocorticoids are among the most widely prescribed medications in childhood for their potent anti-inflammatory, antiallergic, and immunosuppressive properties. However, their clinical use requires a delicate balance between therapeutic efficacy and potential adverse effects on growth, metabolism, and endocrine function. This paper examines the pharmacokinetics and pharmacodynamics of glucocorticoids in children, the molecular mechanisms of action, therapeutic indications, dosing considerations, adverse reactions, and strategies for minimizing toxicity. Special emphasis is placed on age-related physiological differences, hypothalamic–pituitary–adrenal (HPA) axis suppression, and the long-term implications of systemic or inhaled glucocorticoid use.